On Two Lost Medieval Serbian Reliquaries The Staurothekai of King Stefan Uroš I and Queen Helen - Popović, Danica (Balcanica - Annual of the Institute for Balkan Studies, 2019)
This essay discusses two lost medieval Serbian staurothekai known only from written sources. One, belonging to the Serbian King Stefan Uroš I, was described as a sumptuous item in the Hungarian spoils of war following their victory over the Serbian army in Mačva in 1268. The other staurotheke, with an extensive inscription, was Queen Helen’s gift to the monastery of Sopoćani, a foundation of her husband Uroš I. Based on the available facts, it has been assumed that this reliquary came into the possession of a Serbian ruler of the House of Branković in the fifteenth century, eventually ending up in the Habsburg geistliche Schatzkammer and playing an important role in the Pietas austriaca programme. It is known from the surviving descriptions that the staurothekai had the shape of a two-armed cross, and were made of gold and lavishly adorned with precious stones. Apart from their substantial material worth, documented with precision, both staurothekai had a distinct sacral meaning and ideological function.